The Battle Against Biofilms: A Focus on Novel Antimicrobial Strategies and Their Mechanisms of Action - Efstathios Giaouris; Olivier Habimana (Antibiotics)
Biofilms represent the predominant mode of microbial growth across a variety of environments, encompassing both natural and anthropogenic settings [...]